Waste water of north-west Russia as a threat to the Baltic. Issue 3 (11th October 2016) - Alekseev, Mikhail; Smirnova, Elena
Abstract : This paper concerns the issue of ecological safety in the Baltic Sea and the danger caused by the nutrients (nitrogen and phosphorus) issuing from the river basin of north-west Russia. The ecological safety and health of water basins are disturbed when excessive amounts of nitrogen and phosphorus are released from waste water. This results in eutrophication, an increased growth of algae, which causes an imbalance in the ecological system. The cities of Russia's north-west region lack the funds to renovate their water treatment systems. A solution is to improve the biological water treatment system by introducing a chemical. The main goal of this research is to implement enhanced biological phosphorus removal from domestic sewage. To do this, the authors suggest using waste from the production of sulfuric acid (H2 SO4 ) at the ammophos chemical plant in Cherepovets (iron sulfate and phosphogypsum) as reagents. One advantage of these reagents is their low cost. In addition, this solves the problem of their recycling and increases the ecological safety of the rivers in north-west Russia and, thus, of the Baltic Sea. The high removal efficiency of all types of phosphorus and total nitrogen from waste water is attributable to features of micelle creation during coagulation.